Is Biomedical Waste Management Knowledge Adequate in Paramedics & Sanitary Workers in Hospitals of Ujjain City? - Rajput, Anand; Deshpande, Kirti; Chakole, Swarupa V; Mehta, S C (National Journal of Community Medicine, 2016)
Background: Hospitals produce a byproduct which is wasteful and causes contamination of the environment, with its antecedent complications. Inadequate and inappropriate knowledge of handling may have serious health consequences. Objectives: Present study was conducted to find out the current level of knowledge among paramedics (Lab Technicians, nursing staff) & sanitary workers in hospitals of Ujjain city regarding biomedical waste management. Methods: A Cross-sectional study was conducted on 400 study participants in the Government and private hospital of Ujjain city from 1st January 2013 to 30 November 2013.Statistical analysis was done by SPSS 16.0 and chi-square test. Results: Mean age of the total 400 study participants was 31.36 (SD=11.62) years, among them 68.5% were female, majority (64.5%) were the nurses and majority (64.7%) were working in the concerned hospital since more than 2 years. Nursing staff has adequate knowledge (36.8%) as compared to lab technician & sanitary staff (30.3%). Staff who had received medical waste management training had significantly (p<0.05) higher knowledge. Conclusion: On the basis of findings, we conclude that the knowledge regarding biomedical waste management is not adequate among nursing staff, lab technicians and sanitary workers.